Research on the Expression of Immune-Related Genes at Different Stages in the Third-Instar Larvae of Spodoptera frugiperda Infected by Metarhizium rileyi - Pengfei Xu; Zhan He; Xuyuan Gao; Xianru Zeng; Dewei Wei; Xiuzhen Long; Yonghao Yu (Insects)
Spodoptera frugiperda is a major migratory agricultural pest that poses a significant threat to global crop safety. Metarhizium rileyi has emerged as an effective biocontrol agent against lepidopteran pests. In this study, we examined the immune responses of third-instar S. frugiperda larvae at various stages of an M. rileyi infection. Using RNA-seq and microscopic observation, we identified the immune-related pathways enriched at different infection stages, which were further validated by a qRT-PCR. Our findings revealed the following immune responses during infection: During the stage when M. rileyi penetrated the host cuticle (0–48 h), the genes related to energy metabolism, detoxification, and melanization were upregulated. Meanwhile, the TOLL and IMD signaling pathways were activated to counter the infection. During the stage of M. rileyi’s internal infection (48–96 h), which was the peak expression period of the immune-related genes, cellular immunity predominated. Hemocytes encapsulated and phagocytosed the hyphal bodies. Phagocytosis was enhanced through the upregulation of the genes related to ROS and the melanization-related genes, as well as the genes involved in insect hormone biosynthesis. During the stage when M. rileyi grew from the inside to the outside of the host (96–120 h), immune system paralysis resulted in host mortality. These findings deepen our understanding of the immune interactions between M. rileyi and S. frugiperda, support the potential of M. rileyi as an effective biocontrol agent, and provide a theoretical foundation for the development of targeted biopesticides for pests using biotechnological approaches.